Training and Mentoring on Meta-Product-Based Digital Marketing Strategies to Increase the Competitiveness of School MSMEs - Bambang Suwarno; Bernard Ekarisman Ndururu; Feby Yoana Siregar; Okta Jaya Hermaja; Herlin Munthe; Kristi Endah Ndilosa Ginting; Muhammad Fikri Akbar Zuhdi; Puji Syukran; Agung Prabowo (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The purpose of this Community Service activity is to improve the understanding and skills of students in grades X, XI, and XII of SMKN 1 Binjai in implementing digital marketing strategies based on Meta products to support the competitiveness of school MSMEs. The implementation method uses a participatory training approach and direct practical mentoring which includes understanding digital marketing concepts, introducing Meta products, creating promotional content, managing customer communications, and evaluating data-based marketing performance. Success was measured through pre-tests, post-tests, group practice observations, and Likert-scale questionnaires to assess the increase in knowledge, skills, and perceptions of participants regarding the benefits of the training. The results of the activity showed an increase in participants' understanding after participating in the training, especially in the aspect of using Instagram, Facebook, WhatsApp Business, and Meta Business Suite as promotional media for school MSMEs. Participants also demonstrated the ability to compose promotional captions, create digital content designs, manage customer communications, and understand performance indicators such as reach, impressions, engagement, clicks, comments, and incoming messages. The results of this training and mentoring have been proven to help students understand digital marketing in a more applicable, creative, and data-driven way. This activity also strengthens students' digital entrepreneurship skills by utilizing the Meta ecosystem as a learning and promotional medium. The limitation of this activity lies in the evaluation, which still focuses on short-term results through pre-tests, post-tests, and participant perceptions. Contributions: This activity provides practical contributions in the form of a digital marketing training model based on Meta products for vocational school students and theoretical contributions in strengthening digital entrepreneurship in schools.